Bounded bodies : the everyday clothing practices of larger women : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sociology, Massey University, Albany, New Zealand - Cain, Trudie Melissa (Massey University, 2011)
The field of dress studies currently emphasises dress as an embodied practice, but surprisingly scant attention has been awarded to the fat fleshy clothed body. This thesis addresses this lacuna, and is concerned with the everyday clothing practices of larger women. Theoretically, I draw on and integrate literature from material culture studies, as well as from the politics of fatness, the latter serving as the socio-cultural foundation for the research. In doing so, my research contributes to and extends the current body of literature that considers dress as material culture. This thesis offers further extension of the field through the methodological focus of the research. Employing multiple inter-related methods allows the complex social processes of larger women?s clothing practices to be revealed. Often these processes are embedded within the seemingly habitual, mundane, everyday things that people do while operating within a particular social milieu. With this in mind, I employ an ethnographically-inspired, multiple-method research methodology to explore the everyday clothing practices of ten self-identified larger women in Auckland, New Zealand. The five research methods involve asking the participants to: keep a clothing journal; rummage through their wardrobe with me; go shopping for clothes with me; take photographs of their „clothed worlds?; and take part in a group discussion with other participants. Employing an integrative analytic process, I reveal the numerous ways that larger women enact their agency at the same time as being bound within structures of socio-cultural corporeal and clothing norms. My research shows that the boundaries between fleshy fat bodies, clothing and culturally-bound geographical spaces are experienced by my participants as tension-filled and ambiguous. Ultimately, they are perpetually provisional; the boundaries fixed yet potentially permeable. Using space as an organisational and analytic framework, my research explores the boundaries of four distinct spaces: spaces of consumption; public spaces beyond consumption; private spaces; and the spaces between fat bodies and clothes. I argue that, despite structural barriers that create „fat? bodies as „matter out of place? and, as such, beyond the bounds of possibility, larger women enact agency in creative and resourceful ways. In doing so, they challenge the boundaries of dominant Western constructions of fatness and ultimately, transform places of exclusion into spaces of inclusion.
Keywords: Large women; Overweight women; Women's bodies; Fat bodies; Clothing practices; Clothing; Fatness